2018
DOI: 10.2514/1.g002848
|View full text |Cite
|
Sign up to set email alerts
|

New Closed-Form Solutions for Optimal Impulsive Control of Spacecraft Relative Motion

Abstract: This paper addresses the spacecraft relative orbit reconfiguration problem of minimizing the delta-v cost of impulsive control actions while achieving a desired state in fixed time. The problem is posed in relative orbit element (ROE) space, which yields insight into relative motion geometry and allows for the straightforward inclusion of perturbations in linear timevariant form. Reachable set theory is used to translate the cost-minimization problem into a geometric path-planning problem and formulate the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…They proposed a general methodology, based on the inversion of relative dynamics equations, which led to the straightforward computation of analytical or numerical control solutions. A similar impulsive approach based on the ROE parameterization is developed by Chernick and D'Amico in [3]. Here, the authors extended the results reported in [2], deriving the analytical and semi-analytical solutions for in-plane and out-of-plane reconfigurations, respectively, in near-circular J 2 perturbed and eccentric unperturbed orbits.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…They proposed a general methodology, based on the inversion of relative dynamics equations, which led to the straightforward computation of analytical or numerical control solutions. A similar impulsive approach based on the ROE parameterization is developed by Chernick and D'Amico in [3]. Here, the authors extended the results reported in [2], deriving the analytical and semi-analytical solutions for in-plane and out-of-plane reconfigurations, respectively, in near-circular J 2 perturbed and eccentric unperturbed orbits.…”
Section: Introductionmentioning
confidence: 82%
“…Then, the relative state vector δα consists of the relative semimajor axis δα the relative longitude δλ as well as the coordinates of the relative eccentricity vector δe and relative inclination vector δi, respectively. The preceding relative state is nonsingular for circular orbits (e c 0), whereas it is still singular for strictly equatorial orbits (i c 0) [3]. The averaging theory [13] can be used to derive the variation of the mean ROE due to the Earth's oblateness J 2 [7,14].…”
Section: A Relative Dynamics Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…For the most part, preliminary mission design methods rely on lowfidelity dynamical models, which in turn, frequently leads to analytical propagation of the state dynamics through Keplerian orbit models [20] or by utilizing the solution of Lambert's problem [21][22][23][24][25]. Impulsive maneuvers are also used extensively for formation flight optimal control problems [26][27][28][29][30][31][32][33][34][35][36] and orbit reachability analyses problems [37][38][39][40][41][42][43].…”
mentioning
confidence: 99%